Thrombospondin Induces Dimerization of Membrane-Bound, but not Soluble CD36 - Daviet, L; Malvoisin, E; Wild, T F; McGregor, J L (Thrombosis and Haemostasis, 1997)
CD36 is a cell surface receptor that has been shown to interact with a large variety of ligands including thrombospondin, collagen, Plasmodium falciparum-infected erythrocytes, apoptotic neutrophils, modified low density lipoproteins, anionic phospholipids and long chain fatty acids. A number of these CD36 ligands elicit the transduction of intracellular signals involved in cell activation and internalization of bound ligands. The engagement of CD36 possibly activates three cytosolic protein tyrosine kinases that are presumably associated with the C- terminal cytoplasmic tail of CD36. However, the mechanisms by which CD36 functions in ligand binding and signal transduction are poorly understood. In the present study, a membrane-bound and a truncated soluble form of CD36 were expressed in HeLa cells and analyzed by velocity-gradient centrifugation and chemical cross-linking. We show that membrane CD36 exists predominantly as a monomer but a homo- dimeric form is also found. In contrast, soluble CD36 sedimented in sucrose gradient as a monomer. However, when incubated with thrombospondin, the membrane form of CD36 predominantly sedimented as a dimer whereas soluble CD36 was monomeric. This study shows that thrombospondin has the ability to induce dimerization of CD36 and may be implicated in the signal transduction capacity of this adhesion molecule.